Measuring Image through House Design Approach and Resident Satisfaction of Puri Al-Fatih Residential Covid-19 Pandemic Time - Suri Nurmawan Sipahutar; Pristiyono Pristiyono; Eva Fitria; Mulkan Ritonga (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study is to measure the marketing concept applied by the management of Puri Al-Fatih Housing through the house design approach and occupant satisfaction and accommodation to the image of Puri Al-Fatih Housing. The sample used is 70 people who are residents who live in Puri Al-Fatih Housing. Measurement of the instrument was carried out thoroughly with validity and reliability tests. The data analysis technique used path analysis (SPSS and Amos). The results of the study found that the house design variable had a significant effect on the occupant satisfaction variable with a coefficient of 0.540> 0.05. The home design variable has a significant effect on the image variable with a path coefficient between 0.460 > 0.05. Finally, the occupant satisfaction variable has a significant effect on the image variable with a path coefficient of 0.277> 0.05. The implication of this research shows that the house design variable has a coefficient value compared to other tested variables so that the home design variables can be shown which can be the right variables in measuring occupant satisfaction and image.